Brain-derived extracellular vesicles potentially mediate crosstalk with peripheral organs in neurodegenerative diseases - Hamdalla, Ramzi H.; Bhaskar, Vibha B.; Tian, Changhai (Frontiers in Cell and Developmental Biology, 2026)
Brain-Derived Extracellular vesicles (BDEVs) are emerging mediators of intra- and interorgan communication in neurodegenerative diseases (NDs) such as Alzheimer’s Disease (AD) and Parkinson’s Disease (PD). A growing body of evidence suggests that BDEVs play an important role in modulating intercellular communication within the central nervous system in the pathogenesis of many NDs. By transporting non-coding RNAs (e.g., miRNAs) and important pathological proteins, BDEVs also influence peripheral organs and contribute to the progression of disease in the central nervous system (CNS). This review extends the understanding of NDs beyond solely brain dysfunction and gives a novel framework for the progression of these diseases, uniquely emphasizing the currently underexplored mechanisms by which BDEV-mediated communication exacerbates or potentially initiates peripheral dysfunction or complications. It maps and clarifies the specific and potential mechanisms by which CNS-originating EV activity proliferates systemic dysfunction, presenting new opportunities and areas for therapeutic and diagnostic treatments for NDs. These findings are contextualized across multiple NDs, including Amyotrophic Lateral Sclerosis (ALS), Huntington’s Disease (HD), and Multiple Sclerosis (MS), by incorporating data on dysregulated BDEV miRNAs and toxic proteins to map the pathway of BDEV-mediated disease spread.